1997
DOI: 10.1038/40153
|View full text |Cite|
|
Sign up to set email alerts
|

Ataxin-1 with an expanded glutamine tract alters nuclear matrix-associated structures

Abstract: Spinocerebellar ataxia type 1 (SCA1) is one of several neurodegenerative disorders caused by an expansion of a polyglutamine tract. It is characterized by ataxia, progressive motor deterioration, and loss of cerebellar Purkinje cells. To understand the pathogenesis of SCA1, we examined the subcellular localization of wild-type human ataxin-1 (the protein encoded by the SCA1 gene) and mutant ataxin-1 in the Purkinje cells of transgenic mice. We found that ataxin-1 localizes to the nuclei of cerebellar Purkinje … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
348
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 512 publications
(373 citation statements)
references
References 26 publications
(24 reference statements)
20
348
0
3
Order By: Relevance
“…ATXN1 is an RNAbinding protein thought to act as a transcriptional repressor (Yue et al, 2001;Irwin et al, 2005). The expression of pathogenic ATXN1 protein carrying expanded tracts of polyQ results in Spinocerebellar Ataxia type 1 (SCA1), a disease that decimates cerebellar Purkinje cells and brain stem neurons (Skinner et al, 1997). Therefore, it is likely that HMGA1 might have a certain role in the development of the cerebellum, even though Hmga1-null mice do not show a gross impairment of the cerebellar functions.…”
Section: Discussionmentioning
confidence: 99%
“…ATXN1 is an RNAbinding protein thought to act as a transcriptional repressor (Yue et al, 2001;Irwin et al, 2005). The expression of pathogenic ATXN1 protein carrying expanded tracts of polyQ results in Spinocerebellar Ataxia type 1 (SCA1), a disease that decimates cerebellar Purkinje cells and brain stem neurons (Skinner et al, 1997). Therefore, it is likely that HMGA1 might have a certain role in the development of the cerebellum, even though Hmga1-null mice do not show a gross impairment of the cerebellar functions.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were carried out according to a protocol approved by the animal care committee of the Minister of Public Health, and in accordance with guidelines from the European Union and NIH guide for care and use of laboratory animals. In all experiments, control mice were (Skinner, 1997) wild-type mice and single transgenic, expressing only the activator tTA protein or carrying the responder transgene, because these did not show any difference in all the behavioral and morphological analyses performed.…”
Section: Animalsmentioning
confidence: 99%
“…Characteristic neuropathological findings in SCA1 are the loss of Purkinje cells in the cerebellum and neurons in the inferior olivary complex (Robitaille et al, 1995). As described for other polyglutamine diseases such as Huntingdon's disease (HD) Davies et al, 1997), the presence of neuronal intranuclear inclusions (NIs) in Purkinje cells in human patients and in a transgenic mouse model (Skinner et al, 1997) represents a pathological hallmark of SCA 1. Recent evidence shows that compounds that increase inclusion formation might reduce cellular pathology in several neurodegenerative disorders (Bodner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The blots were incubated with anti-ataxin 11NQ polyclonal antibody (1:5000 dilution) [17] and anti-polyQ 1C2 MoAb (1:6000 dilution) [20], followed by a horseradish peroxidase (HRP) labeled second antibody (1:1000 dilution). Immunodetection was carried out with the enhanced chemiluminescence Western blot system (Amersham Pharmacia).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Despite the wide expression pattern of ataxin-1, a selective degeneration of cerebellar Purkinje cells and brainstem neurons can be found in SCA1. The analyses of the subcellular localization of ataxin-1 in the Purkinje cells of SCA1 transgenic mice, neurons of SCA1 patients, and in transfected COS-1 cells, have revealed that normal ataxin-1 localizes to several nuclear structures and that it associates with the nuclear matrix, whereas the expanded ataxin-1 localizes in a few large structures, in the affected neurons [17].…”
Section: Introductionmentioning
confidence: 99%